3
$\begingroup$

Let $G$ be a finite group, let $B,N,H$ be subgroups of $G$. I believe that $$ \langle B \cap H, N \cap H \rangle = \langle B,N \rangle \cap H $$ but I do not find a satisfactory proof. I think this may be useful. I tried to use it but I did not manage to write a 100% satisfactory proof. Can someone help me with it?

Thanks in advance.

$\endgroup$
11
$\begingroup$

This is false. Let $G=\mathbb{Z}/2\mathbb{Z}\times\mathbb{Z}/2\mathbb{Z}$, let $B=\langle (1,0)\rangle$, $N=\langle (0,1)\rangle$, and let $H=\langle(1,1)\rangle$. Then $$\langle B\cap H,N\cap H\rangle=\langle \{(0,0)\},\{(0,0)\}\rangle=\{(0,0)\}$$ but $$\langle B,N\rangle \cap H= G\cap H=H=\{(0,0),(1,1)\}$$

$\endgroup$
  • 3
    $\begingroup$ Took the symbols right out of my browser... $\endgroup$ – Arturo Magidin Apr 29 '11 at 19:40
  • $\begingroup$ @Arturo: LOL! :) $\endgroup$ – Zev Chonoles Apr 29 '11 at 20:04
4
$\begingroup$

This is false. Let G be the non-abelian group of order 6. Let B,N be distinct Sylow 2-subgroups of G, and let H be the Sylow 3-subgroup of G. Then B∩H=N∩H=1, but ⟨B,N⟩∩H=G∩H =H.

A related and true statement is called Dedekind's modular law.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.